Pentingnya Empati dalam Membangun Hubungan Sosial di Lingkungan Sekolah - Alnim, Maria Agnes; Wenyi Rohi, Enasely Mega (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
. Empathy is the ability to understand and feel the feelings of others, which forms the basis for harmonious social relationships in educational environments. This study aims to examine the role of empathy in building social relationships among students at school and its implications for character development and a positive learning climate. The method used is library research by analyzing ten national journals that discuss the relationship between empathy, prosocial behavior, communication, psychological well-being, and inclusiveness in schools. The results of the study show that empathy plays an important role in preventing conflict and bullying, encouraging prosocial behavior, strengthening effective communication, improving psychological well-being, and building an inclusive learning environment. Empathy has also been proven to be developed through social-emotional learning strategies, role-playing methods, and teachers' exemplary behavior. Thus, empathy education not only contributes to the character building of students, but also creates a more humanistic and tolerant school culture that supports the growth of social solidarity among individuals.